Adverse effect of poor waste water management practise on the Tunggak River Pahang, Malaysia - Lydiaizna, Adam (2015)
River is an example of surface water that played as one of the water sources and supply to community. Currently, many rivers in Malaysia have been deteriorated due to a few factors that have exerted immense pressures on water quality. The purposed of this study was to investigate the adverse effect of poor waste water management practise on the Tunggak River water quality. The main objectives of this research was to investigate the status of water quality based on National Water Quality Standard (NWQS) and Water Quality Index (WQI) and also to define the sources of pollutant discharged into the river in order to manage and protect the surface water from contamination. To achieve the objectives, samples from the Tunggak River were collected and involved in situ and ex situ parameters. In situ parameters were dissolved oxygen (DO), Temperature, pH and turbidity while ex situ parameters was biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), ammoniacal nitrogen (AN), sulphate (SO4 2-) and phosphate (PO4 -3). The results showed that Station 1 and 2 was classified as highly polluted (class IV) and Station 3 was classified as class III (polluted) based on WQI. From the results, it is clear that the industrial waste water is one of the main sources of pollutant into the Tunggak River. According to NWQS, water of the Tunggak River cannot be used except proper treatment.